3-Ketosphinganine provokes the accumulation of dihydroshingolipids and induces autophagy in cancer cells. Issue 4 (1st March 2016) - Ordóñez, Yadira F.; González, Jèssica; Bedia, Carmen; Casas, Josefina; Abad, José Luis; Delgado, Antonio; Fabrias, Gemma
Abstract : R = H, acyl; X = H, D; Y = H, phosphate, phosphocholine, glucose, or lactose. Abstract : Although several reports describe the metabolic fate of sphingoid bases and their analogs, as well as their action and that of their phosphates as regulators of sphingolipid metabolizing-enzymes, similar studies for 3-ketosphinganine (KSa), the product of the first committed step in de novo sphingolipid biosynthesis, have not been reported. In this article we show that 3-ketosphinganine (KSa) and its dideuterated analog at C4 (d2KSa) are metabolized to produce high levels of dihydrosphingolipids in HGC27, T98G and U87MG cancer cells. In contrast, either direct C1 O -phosphorylation or N -acylation of d2KSa to produce dideuterated ketodihydrosphingolipids does not occur. We also show that cells respond to d2KSa treatment with induction of autophagy. Time-course experiments agree with sphinganine, sphinganine 1-phosphate and dihydroceramides being the mediators of autophagy stimulated by d2KSa. Enzyme inhibition studies support that inhibition of Des1 by 3-ketobases is caused by their dihydroceramide metabolites. However, this effect contributes to increasing dihydrosphingolipid levels only at short incubation times, since cells respond to long time exposure to 3-ketobases with Des1 overexpression. The translation of these overall effects into cell fate is discussed.